DAMPAK MEDIA KARTU GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR MURID KELAS II SD NEGERI CIBADAK DI BANDUNG CIWIDEY - Nabila Sri Oktaviani; Ihsan Rizali; Maman Johari (STKIP Subang, 2026)
ABSTRACT This study aimed to determine the effect of picture card media on students' Indonesian language learning outcomes regarding waste classification materials in the second grade of elementary school. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research sample consisted of 35 students, including 20 students in the experimental class and 15 students in the control class. Data were collected through tests, observations, questionnaires, and documentation. The research instrument was proven to be valid and reliable with a Cronbach's Alpha value of 0.762. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene's homogeneity test, the Mann-Whitney U test, and the N-Gain test with SPSS version 26. The findings revealed that the average posttest score of the experimental class was 83.05, which was higher than the control class average score of 58.67. The Mann-Whitney U test produced an Asymp. Sig. (2-tailed) value of 0.000 (<0.05), indicating a significant difference in learning outcomes between the two groups. The N-Gain analysis showed that the experimental class achieved an average score of 0.6964, categorized as moderate and close to high, whereas the control class obtained an average score of 0.4166, categorized as moderate. Observation results reached 85% in the very good category, while questionnaire responses reached 81.93%, also categorized as very good. These findings indicate that picture card media effectively improve students' learning activities, learning interest, and Indonesian language learning outcomes. Therefore, picture card media can be considered an effective instructional medium for elementary school learning. Keywords: picture card media, learning outcomes, Indonesian language, elementary school, quasi experiment